The features of economic growth in the case of Latvia and Lithuania - Irena Danileviciene; Natalja Lace (Journal of Open Innovation: Technology, Market, and Complexity, 2017)
Innovation based growth and development is a hot topic in all economies of the world. Openness of mind, openness of businesses and openness of innovation are the key characteristics and success factors of the global world today. Growth and development strategies are becoming smarter transforming economy towards creation of higher added-value products, services and more effective use of resources. Such a high-priority aim may be achieved by R&D activities, which raise the innovation growth and, positively influence productivity, thus providing a platform for sustainable growth and development. Productivity is perceived as the ability to properly use the production factors to create value-added, implement innovations and to maintain the country's competitiveness. In the macroeconomic researches of different scholars (Solow, Saliola, Seker, Kathuria, Puharts etc.) special attention is given to the quantitative measurement of the various factors of growth and development. These researches have shown that one of the more accurate methods of the productivity measurement is a calculation of total factor productivity (TFP). TFP notion is closely related to the innovation concept as proved by many empirical researches. Industry and firm-level studies concluded that R&D investments to a great extent determine TFP growth. The aim of this research is to calculate the total factor productivity by industry both in Latvia and Lithuania for better understanding of economic growth and development perspectives in those countries.
Keywords: 650; Economic growth and development; Gross domestic product; Productivity; Innovations; Total factor productivity